Pengembangan E - Commerce Dengan Pemanfaatan Sistem Payment Gateway (Studi Kasus: Wisata Kampung Sapi Adventure) - Yuninda Eka Nisrina; Widhy Hayuhardhika Nugraha Putra; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Kampung Sapi Adventure Tourism is a cow farm that used as a place for educational tourism objects and develops the concept of agritourism. Currently it does not have information system used for promotional media, booking tickets online, and making financial reports. Buying and selling tickets and bookings through social media are still done manually, therefore, tourists send photos of proof of transfer payments.Then the tour officer will input the ticket purchase transaction data into spreadsheet. This manual process can cause invalid data, because officers are less careful about entering data. This research, an e-commerce application will be built by utilizing the midtrans payment gateway to facilitate the data collection of tourists in the case of buying and selling tickets and reservations as well as making it easier for tour officials to record ticket sales transaction. This researcher uses a Service Oriented Architecture.This research develop requirement analysis, design, implementation, and testing of the system. The testing methods uses are blackbox and compatibility. The test results on this application indicate alignment between system design and applications, and can be run on multiple browsers.